COMICS ABOUT THE RUSSIAN-UKRAINIAN WAR: EDUCATIONAL POTENTIAL (based on the comics ‘Cyborgs’) - Derkachova, Olga (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2025)
The purpose. The article deals with the educational and pedagogical possibilities of comics devoted to the russian-Ukrainian war, and provides an analysis of the series of comics ‘Cyborgs’ describing the events of 2014 in the DAP, as well as the first months of the full-scale invasion. Attention is focused on understanding the role of military/war comics in the contemporary cultural and artistic space. The structural features of comics about war, including documentary comics, are identified. Research methods. The paper uses a system of historical, hermeneutical and structural methods. The author relies on the theoretical and empirical scientific methodology, uses the methodology of literary cognitive science, which is determined by the specifics of this study. Results of the study. The paper helps to identify the peculiarities of the comics about the russian-Ukrainian war ‘Cyborgs’, the specifics of documenting events in them, the peculiarities of structuring panels in which word and picture complement each other, the use of distinguishing markers to depict ‘our own’ and ‘others’, as well as the peculiarities of introducing characters. Originality of the study is an approach to examine and analyse the comics ‘Cyborgs’ not only as an art product, but also as a documentary literature, to identify the specifics of documentation of events in this series, and to follow the connection between the visual and the verbal. The paper emphasises the importance of using such comics in the educational process, as they not only actualise patriotic narratives, but also contribute to the formation of a new culture of reading and dialogue with students on the topics of war, identity and social responsibility. The practical significance of the article lies in the possibility of using the results of the study in research and educational courses dealing with the study of contemporary literature, comics, and the events of the Ukrainian-Russian war, as well as at teacher professional development courses.